Organ Donation Application for Top Glove and Global Doctor (Tggd) Medical Centre - Sasitharan, Pooraani; Bin Hamzah, Dr. Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2022)
Waiting for a long time to get a suitable organ donor specifically liver and kidney is really stressful. Especially during this Movement Control Order (MCO) period. To solve this issue, Organ Donation Application was developed for Top Glove and Global Doctor (TGGD) Medical Centre.The operation unit is still using manual method which means all the documents and reports of the donors are kept in file and organized by the unit staff. Implementation of this traditional method had brought up a lot of problems to the operation unit as well as to the donors and recipients. Some of the major problems are loss of data such as donors medical report and details, absent of organ donation application can make difficulty for searching a suitable donor and final problem is failed to generate statistical report for audit purpose.Next for the objective this project holds three objectives.The first objective is to design an android application for the organ donor to donate organs.The second is to develop a mobile application that can provide platform that can save time to reach desired organ donor.The final is to evaluate an effective method to create awareness towards organ donation.The development of this project will instantly solve the problem faced by TGGD Medical Centre. For the physical design of this application is being constructed using a mobile-based technology, which are phpmyadmin, mySQL and JavaScript and PHP language. The methodology used in developing this application system is Object-Oriented System Development (OOSD) which involves four phases which are Object-Oriented Requirement Analysis, Object-Oriented Design, Object Oriented Implementation and Object-Oriented Testing. To conclude, this application will increase the awareness among others to become a donor and can find a suitable organ donor in a short period.